2020
DOI: 10.1177/1468087420970376
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of isobaric combustion strategy in a compression ignition engine

Abstract: Three-dimensional computational fluid dynamic simulations were conducted to study the means to achieve isobaric combustion mode in a compression ignition engine, which is intended to be used in the high-efficiency double compression-expansion engine (DCEE) concept. Compared to the conventional diesel combustion mode, the isobaric combustion mode generated a significantly lower peak combustion pressure, which was beneficial for the high load extension. For both combustion modes, the ignition was triggered downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, one challenging concern is that soot emissions increased with isobaric combustion [20]. While several studies demonstrated the performance analysis and emission characteristics of isobaric combustion using multiple injections [11,12,21,22], the following research questions need better understanding from optical diagnostics perspective:…”
Section: Introductionmentioning
confidence: 99%
“…However, one challenging concern is that soot emissions increased with isobaric combustion [20]. While several studies demonstrated the performance analysis and emission characteristics of isobaric combustion using multiple injections [11,12,21,22], the following research questions need better understanding from optical diagnostics perspective:…”
Section: Introductionmentioning
confidence: 99%
“…Due to lower peak cylinder temperature, the NOx emissions can be reduced with a limitation of soot emissions. While several previous studies [18][19][20][21][22] addressed the engine performance and emissions of isobaric combustion using multiple injections from a single injector, in-cylinder visualization remains limited. It was reported in previous studies [23,24] that successive fuel injection events in the high-temperature reaction zones enhanced the localized fuel-air rich mixtures which led to increased soot emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Lam et al [14,20,22] reported that for the DCEE concept the isobaric combustion mode performed better compared to the CDC mode since it could generate higher exhaust energy that could be recovered at the expansion stage. However, studies on the isobaric combustion mode are still very limited and most of them [27,28,49] adopted a peak combustion pressure no higher than 150 bar. With the help of CFD tools, this work focuses on exploring the isobaric combustion mode with a significantly high peak pressure of about 300 bar.…”
Section: Resultsmentioning
confidence: 99%
“…However, such a high peak combustion pressure is still a challenge in practical experiments due to the mechanical limit of the metal engine body. To guide the practical engine design, it is better to conduct 3D simulations beforehand, which helps to expedite the optimization of engine parts and control parameters [27,28]. Additionally, due to the excessive pressure rise rate under the CDC mode, it is desirable to adopt an isobaric combustion strategy [21]; however, this brings about more complexity of injection control strategy since multiple injection events are needed to achieve isobaric combustion [29].…”
Section: Fig 1 Schematic Of the Dcee Concept With A 4-4 Stroke Setupmentioning
confidence: 99%
See 1 more Smart Citation